Historical, Curricular and Conceptual Evolution of School Physical Education: A Spanish View - Carrillo-López, Pedro José; Rosa-Guillamón, Andrés; García-Cantó, Eliseo (Acta Paedagogica Vilnensia, 2023)
Current school Physical Education is the evolutionary result of a diversity of social, educational, economic, cultural, religious and military developments following transformations since primitive societies. Analysing its historical, curricular and conceptual evolution is essential for teachers, providing them with a historical basis for reflection of the challenges facing school Physical Education in the 21st century. From this analysis it can be seen that we find ourselves in a current reality with different objectives from the era that preceded it. Once the challenge of offering an education for all at the end of the 20th century has been overcome, it is necessary to carry out didactic approaches adjusted to the needs of the students; consequently, they will be aware of maintaining a progressive responsibility and autonomy in the care of their body; physically and psychologically stimulating their motor development and cognitive capacity. In this way, a didactic transposition of the learning learnt at school to its application in real life will be generated, and more specifically so that Spanish pupils will be at the same level as the European average in a future that looks very competitive. Faced with this scenario, the ever-decreasing demands placed on students, where it is increasingly easier to pass without effort, simply to eliminate failure, logically leads to a student body that is analogue, uncritical and often lacking in enthusiasm for learning. For this reason, Physical Education teachers must shed light on this situation by giving critical intentionality to their pedagogical approaches.
Keywords: Physical Education; epistemology; schoolchildren; health; motor skills